Eve Duncan: A Face to Die For - Book 28 - Johansen, Iris (New York : Grand Central Publishing, 2022)
"Archaeologist Riley Smith has been obsessed with Helen of Troy since she was a small girl, trailing her professor father all over the world in search of the tomb of the world's most beautiful woman. Professor Smith set out to prove that, instead of a myth, Helen had been a living, breathing queen who inspired Homer to write The Iliad. Forensic sculptor Eve Duncan has the unusual skills needed to recreate the face that launched a thousand ships-revealing Helen's true appearance for the first time in history. But convincing Eve to take on the challenge will be difficult because her efforts will come at great personal cost. When tomb raiders murder Riley's father, she is determined to reach the burial site first, get revenge for his death, and enlist Eve's help. Also on hand to help is her father's associate Michael Cade, but he has his own secret agenda when it comes to finding Helen. Now both Riley and Eve are in danger and in a race across one of the most remote parts of the world. At least they have their trust in each other as they hunt for Helen"--
Keywords: Novels